Unlocking the Potential of Chest MRI: Strategies for Establishing a Successful Practice - Kyubin Kim; Kun-Il Kim; Ji Won Lee; Yeon Joo Jeong (Journal of the Korean Society of Radiology)
Chest MRI is a valuable tool for assessing chest structures, particularly when CT produces inconclusive results. MRI provides exceptional soft-tissue resolution and enables the determination of lesion location, size, and invasion into neighboring structures. Its applications span various clinical scenarios, including the differentiation of non-tumorous and tumorous conditions in the mediastinum or pleura, planning of surgical interventions and treatments for such tumors, evaluation of post-treatment recurrence, staging of lung cancer, and diagnosis of progressive massive fibrosis. Despite the technical hurdles posed by cardiac and respiratory motion, advancements in sequence and scan techniques have enabled high-quality chest MRI examinations to be conducted across diverse clinical settings. This pictorial essay aims to offer comprehensive resources and strategies for radiologists to integrate chest MRI into clinical practice and to overcome its present challenges.